2012
DOI: 10.1007/s11999-012-2388-2
|View full text |Cite
|
Sign up to set email alerts
|

Cis-2-decenoic Acid Inhibits S. aureus Growth and Biofilm In Vitro: A Pilot Study

Abstract: Background Cis-2 decenoic acid (C2DA) disperses biofilm in many strains of microorganisms. However, whether C2DA inhibits bacterial growth or has potential to boost the actions of antibiotics is unknown. Questions/purposes We asked whether (1) C2DA inhibited MRSA growth and biofilm, (2) antibiotics increased inhibitory effects, (3) inhibitory concentrations of C2DA were cytotoxic to human cells, and (4) effective concentrations could be delivered from a chitosan sponge drug delivery device. Methods Broth conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 47 publications
3
80
1
1
Order By: Relevance
“…It was found to be bacteriostatic at 125–500  μ g ml −1 against methicillin‐resistant Staphylococcus aureus and its biofilm, without significant cytotoxicity on human dermal fibroblasts (Jennings et al . 2012). In separate studies, Davies and Marques observed dispersion of biofilms formed by Pseudomonas aeruginosa PAO1 by using cis‐2‐decenoic acid at a native concentration of 2·5 nmol l −1 .…”
Section: Discussionmentioning
confidence: 99%
“…It was found to be bacteriostatic at 125–500  μ g ml −1 against methicillin‐resistant Staphylococcus aureus and its biofilm, without significant cytotoxicity on human dermal fibroblasts (Jennings et al . 2012). In separate studies, Davies and Marques observed dispersion of biofilms formed by Pseudomonas aeruginosa PAO1 by using cis‐2‐decenoic acid at a native concentration of 2·5 nmol l −1 .…”
Section: Discussionmentioning
confidence: 99%
“…It disperses biofilm in many strains of micro-organisms [39]. C2DA has been reported to inhibit the growth of multidrug-resistant S. aureus and biofilm in vitro [39].…”
Section: Gc-ms Spectroscopymentioning
confidence: 99%
“…It disperses biofilm in many strains of micro-organisms [39]. C2DA has been reported to inhibit the growth of multidrug-resistant S. aureus and biofilm in vitro [39]. In 2006, Karanja et al [40] identified non-adecane from Chy 4-10, a novel Streptomyces isolate from Chyulu National Park, by GC-MS. Nonadecane is a component of the bacteriocin produced by a mixed culture of Aeromonas sp.…”
Section: Gc-ms Spectroscopymentioning
confidence: 99%
“…Cis-2-decenoic acid appears to act as a diffusible signaling molecule that allows biofilm organisms to coordinate gene expression via cell-cell communication. Jennings et al [58] demonstrated in vitro that antibiotics are more effective at preventing biofilm growth when combined with cis-2-decenoic acid. Practically, cis-2-decenoic is challenging to incorporate into a sustained release local delivery vehicle since it is a fatty acid.…”
Section: Antifouling Agentsmentioning
confidence: 99%